Rancang Bangun Sistem Pakar Fuzzy Untuk Diagnosis Penyakit Tropis Berbasis Web - Putra, Burhanuddin Surya; jusak, Jusak; Tjandrarini, A. B. (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
The tropical disease is a unique desease which often happen in tropical area. There are many types of symptoms of tropical disease which are almost similar. Somehow, it is difficult for common people to diferenciate between tropical disease. Therefore, tropical disease are not easy to be identified. A patient needs a doctor consultation and treatment in order to identify the specific diseases that are suffered. However, time of consultation, distance, and cost are several other things that need to be considered by the patients. To provide simplicity for the patient consultation, It is neccessary to build a fuzzy expert system for diagnosing the tropical disease. Fuzzy expert system for diagnosis of tropical disease by web based. The fuzzy expert system will diagnose each symptom which has been perceived by patient by providing the certainty factor value in every symptom, as well as certainty factor value of the patient answer. Based on the sequence of rules, the system will result in a diagnosed tropical disease. Our examination shows that the system gives accuracy of diagnosing at arround 93,3% . The sample was taken from 15 patients and 2 doctors. The system is able to suggestion treatment based on the type of tropical diseases which are suffered by patients. Additionaly the fuzzy expert system for diagnosing tropical diseases can be accessed at anytime and anywhere utilizing the web browser.